Enhancement the Microstructure and Mechanical Properties for Pb-Sn-Sb Alloys by Using Equal Channel Angular Extrusion - Abood, Adnan Namaa; Abd, Kadhum Ahmed; Mousa, Ammar Nidhal (Al-Nahrain Journal for Engineering Sciences, 2017)
This study aims to enhance the compression strength in one type of Pb-Sn-Sb alloys which wellknown by (Babbitt-ASTM B23 Alloy 13). The ?processing doing via equal channel angular extrusion technique. Three casting were implemented to ?manufacture the alloy; Chill Casting (CC), New Rheocasting (NRC) and Gravity Die Casting (GDC). The ?microscope examination shows that the microstructures contain two phases, ?-Pb and cubic shaped ?intermetallic compound (?-SbSn) in a matrix of ternary phases. CC was fine equiaxed as well as NRC, while ?in GDC was a dendrite ?-Pb phase with remaining ?-SbSn phase as a cubic shape. Higher mechanical properties in compression were recorded for Gravity die casting (12.7 %) while the NRC registered the highest value in yield strength (11.7 %). On the other hand, the casting techniques had a slight difference in Young’s modulus. The other resulted data like hardness showed that NRC is the first reading (12.55 %) and then gravity casting recorded as second score comparing with other (11.79 %), The results ?showed aslo that increasing forming temperature during angular extrusion has an adverse effect on compression ?strength. The study ?concluded that microstructural change caused by ECAP softens the material due to the break-up the original ? precipitate and accelerate from the dynamic recrystallization.